Intake of repeatedly heated palm oil causes elevation in blood pressure with impaired vasorelaxation in rats - Leong, Xin Fang; Najib, Mohd Nadzri Mohd; Das, Srijit; Mustafa, Mohd Rais; Jaarin, Kamsiah (Tohoku University Medical Press, 2009)
Oxidization of dietary cooking oil increases the risk of cardiovascular diseases such as hypertension by increasing the formation oxidative oxygen radicals. The aim of study was to investigate the effects of repeatedly heated palm oil on blood pressure, plasma nitrites, and vascular reactivity. Nitrites were measured, as an indirect marker for nitric oxide production. Male Sprague-Dawley rats were divided into four groups: control group fed with basal diet and other three groups fortified with 15% weight/weight fresh palm oil (FPO), palm oil heated five times (5HPO) or palm oil heated ten times (10HPO) for 24 weeks. The oil was heated to 180°C for 10 min. Blood pressure was measured at baseline and at intervals of four weeks for 24 weeks using non-invasive tail-cuff method. Following 24 weeks, the rats were sacrificed and thoracic aortas were dissected for measurement of vascular reactivity. Blood pressure was elevated significantly (p < 0.05) in 5HPO and 10HPO groups, with the 10HPO group showing higher values. Aortic rings from animals fed with heated oil showed diminished relaxation in response to acetylcholine or sodium nitroprusside, and greater contraction to phenylephrine. Acetylcholine and sodium nitroprusside cause endothelium-dependent and endothelium-independent relaxation, respectively. Relaxation responses remained unaltered in the FPO group, with the attenuated contractile response to phenylephrine, compared to control group. FPO increased plasma nitrites by 28%, whereas 5HPO and 10HPO reduced them by 25% and 33%, respectively. Intake of repeatedly heated palm oil causes an increase in blood pressure, which may be accounted for by the attenuated endothelium-dependent vasorelaxant response.